La coscienza di luogo nel recente pensiero di Giacomo Becattini (2017)
bstract This book was born as a “work in in progress” and collects many of the public presentations of Giacomo Becattini’s book “La cosicenza dei luoghi. Il territorio come soggetto corale” (“The Conscience of Places. The territory as a choral subject”), published by Donzelli in 2015. The presentations inspired great methodological passion, concrete perspectives and also criticism. In fact, the text of Becattini has raised issues of great importance on the perspectives of local development, by projecting them on the very future of human societies in a period of crisis and global uncertainty. The richness, the plurality of accents and the depth of the debate that has developed ensure that the collection lives a “life of its own” even with respect to the book of origin. Becattini’s disappearance, which occurred just as the volume was being edited, leaves a huge void but stimulates even more the debate on this fresco, painted by several artists on the trace of his recent work.